Effect Of The Playing Approach On Underhand Volleyball Passing Learning Result Of Students Sma Negeri 1 Palipi, Samosir District In 2024 - Simbolon, Atur; Suharta, Asep (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research aims to examine the effect of the play-based approach on improving learning outcomes in volleyball underhand passing among 11th-grade students. The study used a quasi-experimental method with a two-group pretest-posttest design. The instrument used to collect data was a one-minute underhand passing observation test. Data were gathered through tests administered before and after the intervention to evaluate how the play-based approach affected the volleyball passing skills of 11th-grade science students at SMAN 1 Palipi. This method was chosen to assess the effectiveness of the play-based approach in enhancing learning outcomes. Hypothesis testing was conducted using One-Way ANOVA, which showed a significant result (0.001 < 0.05), indicating a difference and improvement in volleyball underhand passing skills among students in the experimental group through the play-based approach. The study concluded that the use of the play-based approach significantly improved the volleyball underhand passing learning outcomes of 11th-grade students at SMA Negeri 1 Palipi, with the experimental group achieving better results than the control group.